Exploring schizophrenia and language disorder in the main character of A Beautiful Mind (2001) film: A psycholinguistic study - Lathifah, Arzeta Zulfa; Rahayu, Famala Eka Sanhadi (Ilmu Budaya: Jurnal Bahasa, Sastra, Seni, dan Budaya, 2025)
This research investigates language difficulties brought on by schizophrenia as they are represented in the character John Nash from the 2001 movie A Beautiful Mind. Finding signs of a language disorder in the main character's speech patterns, such as paralogia, affective flatness, and disordered speech patterns, is the goal. Selected conversation and scenes from the movie are analyzed as data in this qualitative descriptive study. According to the analysis, schizophrenia severely hinders communication skills by causing problems with speech coherence and emotional expression. This study advances our knowledge of the relationship between language and psychological diseases and emphasizes the significance of truthful media portrayals in lowering stigma toward people with schizophrenia. Programs for mental health education and awareness could use the practical consequences as a guide.